1985
DOI: 10.2105/ajph.75.7.732
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analysis of a thalassemia disease prevention program.

Abstract: We offer an economic perspective on prevention of p-thalassemia disease by means of genetic screening and prenatal diagnosis in an established program in Quebec province. The program screens 80 per cent of at-risk persons in the high-risk communities, provides diagnosis to 75 per cent of at-risk couples, and prevented two-thirds of new cases in the period of study. We measured the additional costs, in 1981 Canadian dollars, of medical and public health resources, both incurred and avoided, resulting from use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 9 publications
0
30
0
1
Order By: Relevance
“…40 The benefits of accurate diagnosis of iron deficiency and other hemoglobinopathies -hemoglobin S and β-thalassemia in particular -should also be considered. Costbenefit analyses of β-thalassemia prevention programs in Quebec, 41 Iran, 42 Israel, 43,44 and the United Kingdom 45 have generally confirmed the overall benefits of such programs (i.e., the costs of prevention were lower than the costs of treatment), but the studies did not include α-thalassemia. In low-and middle-income countries, the implementation of such programs could benefit from existing infrastructures (e.g., ongoing screening programs for phenylketonuria or glucose-6-phosphate dehydrogenase deficiency) or could result in an overall improvement in access to health care for local communities.…”
Section: He a Lth A Nd Economic Bur Denmentioning
confidence: 99%
“…40 The benefits of accurate diagnosis of iron deficiency and other hemoglobinopathies -hemoglobin S and β-thalassemia in particular -should also be considered. Costbenefit analyses of β-thalassemia prevention programs in Quebec, 41 Iran, 42 Israel, 43,44 and the United Kingdom 45 have generally confirmed the overall benefits of such programs (i.e., the costs of prevention were lower than the costs of treatment), but the studies did not include α-thalassemia. In low-and middle-income countries, the implementation of such programs could benefit from existing infrastructures (e.g., ongoing screening programs for phenylketonuria or glucose-6-phosphate dehydrogenase deficiency) or could result in an overall improvement in access to health care for local communities.…”
Section: He a Lth A Nd Economic Bur Denmentioning
confidence: 99%
“…Every year approximately 100,000 children with Thalassemia major are born world over, of which 10,000 are born in India [1]. It is estimated that there are about 65,000-67,000 β -thalassemia patients in our country with around 9,000-10,000 cases being added every year [2][3][4][5][6][7][8]. The carrier rate for β -thalassemia gene varies from 1 to 3% in Southern India to 3% to 15% in Northern India.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-benefit analyses in the UK, 3 12 Sardinia, 42 Greece, 12 and Canada 19 have repeatedly shown that the costs of a nationwide thalassaemia prevention programme based on prenatal diagnosis are trivial when compared with the benefits of reducing treatment costs. This paper aims at carrying out a cost-benefit analysis of combined educational and national prenatal screening programmes for thalassaemia in Israel.…”
mentioning
confidence: 99%